Consumer Empowerment Index in the Telecommunications Sector: The Role Of Socio-Demographic and Lifestyle - Riska Rahma Eka Putri; Megawati Simanjuntak (Jurnal Manajemen Indonesia, 2022)
Consumer empowerment is a benchmark for business, especially in the telecommunications sector, for economic fundamentals. This study aims to analyze the effect of social, demographic and economic characteristics and lifestyles on consumer empowerment in the telecommunications sector. This study applied a cross-sectional study with data collection by online survey. Cluster analysis and logistic regression were used to analyze 100 data. The results showed that consumer empowerment in the telecommunications sector was still relatively low. The average level of consumer empowerment in the telecommunications sector was 51.61, including the capable category. Based on dimensions, the index of information seeking was 80.8, knowledge of laws and consumer protection institutions was 52.8, service selection was 63.8, usage behavior was 71.0, tendency to talk was 43.7, and complaint behavior was 27.7. The full-filled lifestyle had a significant negative effect on consumer empowerment in the telecommunications sector. Thus, respondents who had a lifestyle other than a fulfilled lifestyle had more opportunities to be empowered than a fulfilled lifestyle. This research is a breakthrough in the study of thematic consumer empowerment, so it needs to be developed in the future. Keywords—Consumer Empowerment; Demographics; Economic; Lifestyle; Social